Analisis Kualitas Pelayanan Publik pada Dinas Perpustakaan dan Arsip Provinsi Sumatera Utara - Siahaan, Riana; Isnaini, Isnaini; Adam, Adam (Mahesa Research Center, 2022)
This study aims to analyze the quality and factors that influence public services at the Library and Archives Service of North Sumatra Province. The services available at the North Sumatra Provincial Library and Archives Service are public services, children's services, deposit services, reference services, digital services and mobile library services. The research method used is descriptive research with a qualitative approach. Data collection techniques used observation, study documentation and interviews. Data analysis used descriptive analysis. The results of this study indicate that the quality of public services at the Library and Archives Service of North Sumatra Province refers to Zeithaml's theory, namely from the dimensions: 1) Reliability (reliability); 2) Responsiveness (responsiveness); 3) Assurance (guarantee); 4) Empathy (empathy); 5) Tangibles (physical evidence). Everything has been done well, but the Tangibles dimensions (physical evidence) have not been maximized in the form of the problematic INSLISLITE application, the room temperature is not cold enough, the room lacks lighting. Factors that affect Public Service Services at the Library and Archives Service of North Sumatra Province are: 1) Inadequate facilities; 2) Budget that has not been maximized.